Dragon rider - Funke, Cornelia, 1958- (Funke, Cornelia, 1958- Drachenreiter (Series)., 2004)
After learning that humans are headed toward his hidden home, Firedrake, a silver dragon, is joined by a brownie and an orphan boy in a quest to find the legendary valley known as the Rim of Heaven.